ANALISIS AKUNTANSI PERSEDIAAN BARANG DAGANG CV. DUTA MOTOR - Eddy Iskandar; Ruth Novita Sari Aruan (UNIVERSITAS DHARMAWANGSA, 2022)
This research is entitled accounting of merchandise inventory at CV. Motorcycle ambassador, who is based in the city of Medan. The purpose of this study was to determine whether the system applied to CV. Duta Motor has complied with the principles of financial accounting standards. CV. Duta Motor is one of the companies engaged in the trade sector, especially the trade of Honda motorcycles and spare parts, in carrying out company accounting records using perpetual inventory where every purchase of inventory made is recorded for every transaction. The inventory valuation method used is CV. Duta Motor is a FIFO method which assumes that inventories with initial cost entered will be used first. From this research, some deviations can be found, including there are still errors in determining the cost of inventory and the presentation of inventory estimates in the financial statements. The author draws the conclusion that inventory accounting on CV. Duta Motor has not been implemented in accordance with those stipulated in the Financial Accounting Standards, the company should apply inventory accounting in accordance with the applicable Financial Accounting Standards.